Pipe nozzle design effect to the speed of turbine and output voltage of the pico-hydropower generator system - Lai, Kok Lee (2021)
Renewable energy widely promoted and used worldwide. In Malaysia, hydropower plant and wind turbine power plant only built in a large scale, such as Sultan Mahmud Power Station (Kenyir Dam) and Bakun Dam Power Plant. The world largest pumped storage hydropower plant is located at Virginia in USA, it can produced around 3003MW of electric to recover the demand time. The main idea of this Pico-Hydropower generator system is from the pumped storage hydropower plant and installation of solar panel on the rooftop of houses in Malaysia which called cleantech solar and promoted by PV expert and Tenaga National Berhad (TNB). From the project of cleantech solar, we have the main idea of electric can produced in houses and sell back to the dealer as a profit to be save. In this thesis deal with the study on the pipe design effect to the output voltage of the Pico-Hydropower generator system. The main objective of this project is design a low cost and easy installed pico-hydropower generator system for houses. The second objective of this project also is to test the type and capacity of loads to be supplied by the pico-hydropower and the performance of the developed Pico-Hydropower generator system in terms of Power (W), Voltage (V) and Current (A). Turbine is an important part in the hydropower generator system. The design of the turbine can changed the output result of the hydropower generator system. Pelton turbine and Turgo turbine is the categories of impulse turbine both of this turbine more suitable to implement into this Pico-Hydropower generator system, due to the water pressure, high, and size of design. Next, the piping head design is also important. The pipe head (nozzle) can affect the performance of the Pico-Hydropower generator system, due to the limitation of water to fill up the specific water tank, we have to use out the maximum number of water and time to have a greatest performance in the generator system. By the way, the turbine was printed by the 3d-printer and used the PLA filament. PLA filament used due to it is more commercial and its cheaper compare to the other filament. The PLA filament can form a high impact resistant product which more suitable to the Pico-Hydropower generator system and the impulse turbine. The pipe in this prototype fabricate used the 3d-printer because we can have a customize shape and size and have a roughly result. The disadvantage of use the 3d-printer in piping system is the rough surface in the pipe will affected the output result compare to the clear surface of the PVC pipe or poly pipe. Finally, the Pelton turbine and pipe in 30degree phase and ratio of 3 implemented in the Pico-hydropower generator system.